ROI for a customer relationship management initiative at GST - Jeffery, Mark, 1965- (London : Kellogg School of Management, 2006)
This case "ROI for a Customer Relationship Management Initiative at GST" addresses key issues related to large revenue-generation IT projects. The key topics covered are: measurement of return on investment and project payback period, the decision of what time horizon and hurdle rate to use, the importance of business assumptions in the model, and additional management issues beyond the basic analysis. The case debrief focuses on the strategy of a firm in a high customer-churn environment and the ability of analytical customer relationship management to provide strategic advantage.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Customer relations -- Management -- Case studies; Rate of return -- Case studies